Predicting the legitimacy of wolf recovery. Issue 1 (19th April 2019) - Serenari, Christopher; Taub, Michelle
Abstract : Legitimacy is a prerequisite of sustainable forms of governance. Existing structures and functions of large carnivore governance have often yielded legitimacy deficits. In northeast North Carolina, USA, recovery of the critically endangered red wolf Canis rufus suffers from a legitimacy deficit, chiefly among its critics. This article operationalizes legitimacy and investigates its predictors in the North Carolina red wolf case. We developed a framework that explores three dimensions of legitimacy (input, output and throughput) to simplify the concept within the red wolf recovery and management system. Our challenge was to identify the relevant predictors of legitimacy in totality to improve governance. We analyzed 2577 survey responses from citizens owning property or living within the red wolf recovery area and used multilevel modeling to analyze the relationships between contextual or individual variables and perceived legitimacy. Results revealed that a higher number of red wolf mortalities in a respondent's county may be an ecological predictor of perceived lower legitimacy. Results also indicate that women, formally educated, and smaller parcel‐owning landowners were more likely to find red wolf recovery legitimate. Tolerance of red wolves, normative ethics about red wolf recovery, and the instrumental value of wolves were also strong predictors of legitimacy. We conclude that situating legitimacy at the center of a nested social–ecological system may more accurately reveal expressions of its core elements, criteria, or sources in order to identify and treat the pathologies of large carnivore governance.